2009
DOI: 10.1080/02640410802668650
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate and metabolic responses to moderate-intensity aerobic exercise: A comparison of graded walking and ungraded jogging at a constant perceived exertion

Abstract: In this study, we assessed how ungraded jogging and graded walking at the same rating of perceived exertion (RPE) affect heart rate and oxygen consumption ([Vdot]O(2)). Twenty untrained participants completed a treadmill test to determine peak [Vdot]O(2) (mean = 40.3 +/- 6.3 ml . kg(-1) . min(-1)). Participants completed separate 30-min trials of moderate exercise (RPE of 13 on the Borg 6-20 scale) in random order on the treadmill: graded walking and ungraded jogging. Treadmill speed or grade was adjusted thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…For example, subjects in the current study reported a greater RPE when step rate increased 10% above preferred. However, given the novelty of the modified step rate conditions to the subjects, we believe that this increase in perceived effort may be reflective of increased attentional focus (5), rather than an actual metabolic response (21). Indeed, increasing one’s step rate to 10% above preferred has demonstrated no significant increase in oxygen consumption or heart rate (18).…”
Section: Discussionmentioning
confidence: 96%
“…For example, subjects in the current study reported a greater RPE when step rate increased 10% above preferred. However, given the novelty of the modified step rate conditions to the subjects, we believe that this increase in perceived effort may be reflective of increased attentional focus (5), rather than an actual metabolic response (21). Indeed, increasing one’s step rate to 10% above preferred has demonstrated no significant increase in oxygen consumption or heart rate (18).…”
Section: Discussionmentioning
confidence: 96%
“…The video recording was created by fixing a GoPro camera (Hero3+, GoPro, San Mateo, CA, USA) on the helmet of a person cycling along a series of paths within the gardens, capturing the trail through lawns, trees and flower beds on a sunny afternoon in spring. The video aimed to represent a first person perspective of moving through the gardens and it was filmed at 2.32 m/s to present a moderate exercise level [ 36 ]. The static image condition was composed of a single frame of the dynamic image to avoid discrepancies between images and was used throughout the twenty minutes physical activity period (see Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, run-based protocols, and especially those with limited grade, may be more desirable for individuals unaccustomed to exercising against a severe grade or when the nature of the exercise test is to identify overground speeds associated with exercise prescriptions tailored to individual fitness. These distinctions are important because research demonstrates that ungraded running and graded walking produce different cardiovascular and metabolic responses when conducted at the same rating of perceived exertion (Kilpatrick, et al, 2009). Importantly, relatively little is known about how treadmill protocols utilizing speed to induce maximal work differ from protocols utilizing grade to induce maximal work, especially in regard to perceptual responses.…”
Section: Introductionmentioning
confidence: 99%